Exploring the Causes of Fear in Children Aged 10-12 Years During Medical Examinations: A Phenomenological Study - Nagara, Clements Nicodhemus Garuda; Indrarto, Wikan; Hapsari, Saverina Nungky Dian (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: For most children, the figure of a doctor is considered frightening because of their imagination, previous bad experiences and children’s fear usually related to pain that caused by medical procedures. This condition causes difficulties for doctor in understanding patient’s complaints. Therefore, this study was conducted as an effort to find out the causes of children’s fear when they got examined by a doctor, in order to assist doctor in managing children’s health problems, complaints and needs.Methods: This research uses a qualitative method with a phenomenological approach. Retrieval of research data using in-depth interview techniques which were analyzed by thematic analysis. This research involved 4-6 grader of Tarakanita Elementary School in Magelang with the assistance of subject’s parents and pyschologistResults: In-depth interviews were conducted on 12 research subjects, consist of four (33%) fourth graders, five (42%) fifth graders, and three (25%) six graders. There are three themes, such as the causes of children’s fear, the emotional expression of children’s fear, and the external support of children when they are afraid of being examined. Bad experiences due to medical procedures are the most common cause of children’s fear (91,7%). Meanwhile, the most common trigger for children’s fear is pain (50%), which is influenced by imagination (91,7%)Conclusion: Bad experiences from medical procedures are the most dominant cause of fear in children. Meanwhile, the most common trigger of fear is pain, which is often influenced by the child’s imagination. These findings highlight the need for child-friendly medical practices, including improved communication strategies, familiarize children with the procedure prior to its execution and examination room designs that reduce fear in childrenKeywords: children’s fear; doctor; imagination; bad experiences; medical procedures